Greener, Rapid and Reliable UHPLC using 1-alkyl-3-methylimidazolium-based Ionic Liquids as the Mobile Phase Additives for Simultaneous Determination of Steroids and Antihistamines Residues in Herbal Medicines - Krittaya Nusai (Science Faculty of Chiang Mai University, 2019)
The objective of this research was to develop and validate UHPLC using 1-alkyl-3-methylimidazolium-based ionic liquids as the mobile phase additives for simultaneous determination of steroids and antihistamines residues in herbal medicines. Steroids(prednisolone, dexamethasone) and antihistamines(cetirizine, loratadine) were examined. Various factors such as acetonitrile quantity, ionic liquid concentration, alkyl chain length on imidazolium cation of ionic liquid and UHPLC elution technique were investigated to obtain the optimum condition and to understand the separation mechanism. The separation mechanism involves hydrophobic and electrostatically repulsive interactions. The optimum condition was the mobile phase containing a mixture of 30:70, v/v acetonitrile and 1 mM aqueous ammonium acetate solution at pH 3.0 consisted of 2 mM [BMIm][BF4] as the additive with the gradient flow rate of 0.3 - 0.7 mLmin-1, an analytical column was C18( Kinetex; end capping; 2.6 mm; 2.1 mm i.d. ´ 100 mm), column temperature was 40 °C and UV detection was performed at 230 nm. The proposed method spent 2.07 mL of acetonitrile per 1 analysis which is the lowest quantity of acetonitrile in the mobile phase when compared with the previous methods. The analysis time of 15 minutes was obtained. The regression coefficient (R2) more than 0.9995 within 1.0 - 40.0 mg/mL were obtained for all four analytes. The obtained LOQ values were 1.80, 2.67, 1.90 and 3.23 mg/mL for prednisolone, dexamethasone, cetirizine and loratadine, respectively. The obtained LOD values were 0.58, 0.73, 0.57 and 1.04 mg/mL for prednisolone, dexamethasone, cetirizine and loratadine, respectively. No interferences were presented at their retention times. The accuracy expressed in term of recoveries, the obtained average %recoveries and % relative standard deviation (%RSD) of all steroids and antihistamines in three real herbal medicines were in the range of 84.5 - 110.7 %(n = 9) and within 5.5%, respectively. Precision of method in term of the % RSD of intra- and inter-day variations was within 5.3%. The proposed method could determine 107.40 ± 2.54 mg/mL of prednisolone in Andrographis paniculata, 9.24 ± 0.79 mg/mL of dexamethasone and 14.11 ± 1.24 mg/mL of cetirizine in Curcuma longa linn, 0.48 ± 0.07 mg/mL of prednisolone and 0.30 ± 0.03 mg/mL of dexamethasone in Relieves schmerzen herbal.